2022
DOI: 10.1002/uog.23762
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for fetal brain structures using magnetic resonance imaging: systematic review

Abstract: What are the novel findings of this work?Our systematic review highlights the fact that previously published studies reporting fetal brain reference ranges on magnetic resonance imaging (MRI) were characterized by substantial heterogeneity and low-to-moderate methodological quality, which is similar to the findings reported for ultrasound studies. What are the clinical implications of this work?Future large prospective studies aiming to construct longitudinal growth charts for different fetal brain structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Reconstruction of the microstructure of the fetal CC and its subdivisions in utero is associated with several technical difficulties . In addition, a systematic review found that fetal brain reference ranges on MRI have low-to-moderate methodological quality, increasing the risk of bias and possibly affecting prenatal diagnosis and counseling . Fourth, we did not evaluate the associations between postnatal neurodevelopmental outcomes and structural alterations in the fetal CC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reconstruction of the microstructure of the fetal CC and its subdivisions in utero is associated with several technical difficulties . In addition, a systematic review found that fetal brain reference ranges on MRI have low-to-moderate methodological quality, increasing the risk of bias and possibly affecting prenatal diagnosis and counseling . Fourth, we did not evaluate the associations between postnatal neurodevelopmental outcomes and structural alterations in the fetal CC.…”
Section: Discussionmentioning
confidence: 98%
“…33 In addition, a systematic review found that fetal brain reference ranges on MRI have low-to-moderate methodological quality, increasing the risk of bias and possibly affecting prenatal diagnosis and counseling. 34 Fourth, we did not evaluate the associations between postnatal neurodevelopmental outcomes and structural alterations in the fetal CC. Hence, ongoing work by our team includes conducting a prospective study with a larger sample size of individuals with PE or GH, acquiring fetal whole-brain structural imaging and diffusion MRI data, and examining the association between fetal brain alterations and poor neurobehavioral performance in infants.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite this, MRI remains fundamental in identifying associated abnormalities. [12][13][23][24][25][26] However, in contrast to fetuses presenting with mild to moderate ventricular dilatation, where detecting additional anomalies is very relevant in defining prognosis given the relatively low risk of neurodevelopmental delay, in those with severe ventriculomegaly, who commonly present with several degrees of neurological anomalies after birth, the additional information of MRI may have a lesser prognostic advantage.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the ENSO working group included: Daniele Di Mascio*, 1 Asma Khalil, 2,3 Gianluigi Pilu, 4 Giuseppe Rizzo, 5,6 Massimo Caulo, 7 Marco Liberati, 8 Antonella Giancotti, 1 Christoph Lees, 9,10 Paolo Volpe, 11 Danilo Buca, 8 Ludovica Oronzi, 8 Alice D'Amico, 8 Sara Tinari, 8 Tamara Stampalija, 12,13 Ilaria Fantasia, 12 Lucia Pasquini, 14 Giulia Masini, 14 Roberto Brunelli, 1 Valentina D'Ambrosio, 1 Ludovico Muzii, 1 Lucia Manganaro, 15 Amanda Antonelli, 15 Giada Ercolani, 15 Sandra Ciulla, 15 Gabriele Saccone, 16 Giuseppe Maria Maruotti, 16 Luigi Carbone, 16 Fulvio Zullo, 16 Claudiana Olivieri, 11 Tullio Ghi, 17 Tiziana Frusca, 17 Andrea Dall'Asta, 9,10,17 Silvia Visentin, 18 Erich Cosmi, 18 Francesco Forlani, 19 Alberto Galindo, 20 Cecilia Villalain, 20 Ignacio Herraiz, 20 Filomena Giulia Sileo, 2,21,22 Olivia Mendez Quintero, 2 Ginevra Salsi, 4 Gabriella Bracalente, 23 José Morales-Roselló, 24,25 Gabriela Loscalzo, 24,25 Marcella Pellegrino, 26 Marco De Santis, 26 Antonio Lanzone, 26 Cecilia Parazzini, 27 Mariano Lanna, 28 Francesca Ormitti, 29 Francesco Toni, 30 Flora Murru, 31 Marco Di Maurizio, 32 Elena Trincia, 33 Raquel Garcia, 34 Olav Bennike Bjørn...…”
mentioning
confidence: 99%
“…Although, usually, measurements will already have been made with ultrasound, measuring certain structures at the MRI examination may be of benefit in particular cases 12 . Normal values for several cerebral structures have been defined by MRI 44 . Super‐resolution images 45 and machine‐learning‐based automatic measurement methods have been developed 46 .…”
Section: Performance Of Fetal Mrimentioning
confidence: 99%